Anemia and intestinal parasitic infections in primary school students in Aracaju, Sergipe, Brazil - Reiko Tsuyuoka; J. Wendy Bailey; Alzira M. d'Avila Nery Guimarães; Ricardo Q. Gurgel; Luis E. Cuevas
Anemia is estimated to affect half the school-age children and adolescents in developing countries. The main causes are parasitic infections, malaria, and low iron intake. This study aimed to describe the prevalence of anemia, parasitic infections, and nutritional status of children attending public primary schools in Aracaju, Northeast Brazil. Of 360 students, 26.7% were anemic, and prevalence was higher in children under 8 and over 15 years of age. Overall prevalence of intestinal parasites was 42%, with Ascaris lumbricoides (28.7%), Trichuris trichiura (15.6%), and hookworm (1.7%) most frequently found. There was an association between parasitic infections and poor sanitary conditions, but there was no association between anemia and presence of intestinal parasites. Height-for-age Z scores were lower than the NCHS standard, and prevalence of stunting was 5.4%. Although intestinal parasites were not associated with anemia, children with parasites had lower nutritional indices (weight- and height-for-age Z scores) than those without parasites.